Apocalyptic Imagination and Civic Practices of Orthodox Fundamentalists in Contemporary Russia - Mitrofanova, Anastasija V. (Journal of law and religion, 2024)
Fundamentalists in the Russian Orthodox Church see contemporary state institutions as sources of threat because of their fragility and unreliability. Thus, in response, they engage in ritual and political actions aimed at restoring the spiritual unity of the Russian people (sobornost) that would allow the monarchy to be restored and resume the God-given mission of the Russian Orthodox Church to delaying the apocalypse. In this article, the author reveals the ways the concept of an averted or delayed apocalypse shapes fundamentalists' approaches to institution and network building as alternatives to existing public institutions, which they consider incapable in the face of the approaching End Time. The author distinguishes between anti-systemic fundamentalists (those unwilling to have anything in common with the existing sociopolitical system) and symbiotic fundamentalists (those involved in provisional cooperation with state agencies). Anti-systemic fundamentalists insist on Russians’ verbal repentance for the sin of abandoning their mission of averting the Apocalypse; sometimes they live in walled communities. Symbiotic fundamentalists are building networks or communities that do not necessarily imply living together. Using these communities as a tool, symbiotic fundamentalists hope to rebuild the spiritual unity of the Russians. They envision their activities as repentance by works that in the future would allow the Orthodox monarchy to be restored and to resume the God-given mission of the church.